The role of continuous auditing in limiting creative accounting practices - A field study on a sample of Sudanese banks - - Mohammed, Mohammed Khalil Hamed; Abubakir, Eesa Abdelrahim Oshy; Elhag, Noureldaim Eltayeb Yousif (Journal of Economic, Administrative and Legal Sciences, 2020)
This study dealt with the role of continuous review in limiting creative accounting practices (a field study on a sample of Sudanese banks). The problem of the study is: there are many alternatives to measurement and accounting evaluation that may be used to influence financial data to achieve creative accounting goals, which may affect the interests of some Categories associated with the company. The importance of the study lies in activating the role of continuous review and limiting creative accounting practices in manipulating the list of financial position and income in Sudanese banks. The study followed the descriptive approach, the analytical approach and the case study method, with the use of the (SPSS) program to analyze the data collected by the questionnaire tool from the number (100) random sample from the study population. The study concluded that the continuous verification of the appropriateness of accounting measurement in financial transactions limits the effects of creative accounting in the statement of financial position. Continuous verification of the adequacy of accounting estimates for some financial elements limits the effects of creative accounting on financial statements. The study recommended continuous verification of the appropriateness of accounting measurement in financial transactions limiting the effects of creative accounting in the statement of financial position.